RESOURCE REVIEW. (2nd February 2021) - Cousins, Emily
Abstract : Emily Cousins continues our new resource review column, which will provide a synopsis and brief analysis of a recently published resource that may be of interest to neuroscience nurses; a full reference is provided for those who wish to read the text